Implementasi Pengembangan Kurikulum Pendidikan Agama Islam Berbasis Pendidikan Karakter di SMP Al Azhar Kediri - Kusairi; Bustomi Musthofa; Susiati Alwy (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2019)
The curriculum of Islamic education development is an activity that produces a PAI curriculum or process that links a component to another to produce a better PAI curriculum and activities to compile, implement, evaluate and refine the PAI curriculum. This type of research is a description of the field and uses the cauliflower method, in collecting data using methods of observation, interviews and documents. While the data analysis technique uses editing, verifying and analyzing analysis techniques. The results of this study indicate that the implementation of PAI curriculum development based on character education in Al Azhar Islamic Middle School Kediri is done through three stages, including First, the planning stage is done by determining the background, principles and objectives of curriculum development. Second, the implementation phase is carried out through Intracurricular activities and self-development. Third, the evaluation phase at this stage is carried out in the implementation of intracurricular activities and self-development, evaluation of methods, media and learning resources and evaluation of learning outcomes.